Documenting the Longitudinal Relationship between Group Conflict and Group Cohesion. Issue 3 (4th May 2022) - Manata, Brian; Bozeman, Jessica
ABSTRACT: Group scholars have devoted a considerable amount of attention to the dynamics of group conflict and group cohesion. This investigation contends that both dynamics are closely related, such that they are related causally. A three-wave longitudinal investigation is reported that examines the extent to which this is the case. Results suggest that group conflict has a strong negative effect on group cohesion over time, and that this is the case despite controlling for the effect of past cohesion on future cohesion (i.e., the cohesion autoregressions). Alternatively, the negative effects of group cohesion on group conflict are much more limited and were deemed trivial. These results suggest that group conflict is a strong causal indicator of group cohesion, but that the causal effect of group cohesion on group conflict is much more limited. Future scholarship is encouraged to investigate the extent to which certain variables moderate the group conflict → group cohesion relationship, such that the negative effects of group conflict are attenuated or perhaps reversed.